Pengaruh Independensi, Integritas, Akuntabilitas, Pelatihan Auditor Dan Sikap Skeptisisme Profesional Terhadap Kemampuan Auditor Dalam Mendeteksi Kecurangan - Meidiah Islamiati; Agrianti Komalasari; Rialdi Azhar (Journal on Education, 2024)
This study aims to determine the effect of independence, integrity, accountability, auditor training and professional skepticism on the auditor's ability to detect fraud. this study used 37 samples. sampling in this study using convenience sampling and using multiple linear regression analysis as an analytical tool. this study uses four independent variables to achieve this goal, namely: independence, integrity, accountability, auditor training and professional skepticism. while the dependent variable used is ability to detect fraud. this research was conducted using primary data. data collection was carried out using the survey method, namely by distributing a list of questions (survey) to respondents who served at kaps in southern of sumatra. the results of this study prove that auditor training have a positive effect on the auditor's ability to detect fraud. however, independence, integrity, accountability and professional skepticism have no effect on auditor's ability to detect fraud.